A Critical Examination of the Electronic Evidence Mechanism in Indonesian Procedural Law - Slamet, Amalul Arifin (Universitas Muhammadiyah Tangerang, 2025)
The digital era has profoundly transformed the Indonesian judicial system, particularly in the realm of evidentiary law. The emergence of electronic evidence such as digital documents, online communications, and electronic transactions has enriched the evidentiary framework while simultaneously presenting significant challenges concerning authenticity, integrity, and admissibility. Although the Electronic Information and Transactions Law formally recognizes electronic evidence, inconsistencies arise due to its disharmony with procedural codes such as the Criminal Procedure Code, Het Herziene Indonesisch Reglement (HIR), and Rechtsreglement Buitengewesten (RBg), which remain oriented toward conventional forms of proof. This normative-comparative legal study employs statute, case, and comparative approaches, analyzing Indonesian regulations, judicial decisions, and international standards including the UNCITRAL Model Law, the EU e-Evidence Regulation, and practices in the United States and Singapore. The findings reveal that Indonesia’s regulatory framework remains fragmented, lacking uniform technical standards, forensic capacity, and judicial readiness to effectively assess electronic evidence. Comparative analysis demonstrates that advanced jurisdictions have developed integrated mechanisms such as electronic discovery (U.S.), technology courts (Singapore), and trust service regulations (EU), which ensure greater certainty and reliability. The study argues for comprehensive reform through harmonization of procedural laws, establishment of clear forensic and authentication standards, enhancement of judicial and law enforcement capacity, and adoption of best practices in line with global developments. Strengthening the electronic evidence mechanism is crucial to safeguard legal certainty, fairness, and due process in Indonesia’s judicial system.Keywords: Electronic Evidence, Indonesian Procedural Law, Digital Forensics, Fair Trial, Legal Reform